Effect of Peer Instruction Flipped with e-LKPD on Critical Thinking and Learning Independence in Informatics - Ni Luh Putu Ary Jhuniati; Ni Nyoman Parwati; I Gde Wawan Sudatha (Thinking Skills and Creativity Journal, 2025)
Low critical thinking skills and learning independence pose crucial challenges in 21st-century Informatics education. This study aimed to examine the influence of the Peer Instruction Flipped learning model assisted by Electronic Student Worksheets (e-LKPD) on both competencies. Employing a quasi-experimental post-test only control group design, the research involved a sample of 89 eleventh-grade students. Critical thinking data were collected through an essay test, while learning independence was measured using a questionnaire. Data analysis was conducted using Multivariate Analysis of Variance (MANOVA) at a 5% significance level. Results indicated a significant simultaneous difference in Informatics critical thinking skills and learning independence between the experimental group (Peer Instruction Flipped model assisted by e-LKPD) and the control group (Direct Instruction model). Separately, significant differences were also found in both variables. Student responses towards the Peer Instruction Flipped model assisted by e-LKPD were highly positive. Thus, it is concluded that the Peer Instruction Flipped model assisted by e-LKPD is effective in enhancing critical thinking skills and learning independence in Informatics. The implication of this study is the necessity of integrating innovative technology-based learning models to prepare students for the demands of 21st-century competencies.